Проблема легітимності гуманітарних інтервенцій у сучасних міжнародних відносинах - Здоровега, Мар’яна (Видавництво Львівської політехніки, 2015)
З’ясована сутність поняття «гуманітарна інтервенція» та основні підходи її до інтерпретації. Визначено характер суперечностей щодо легітимності застосування гуманітарних втручань у міжнародному праві та на практиці. Проаналізовано особливості застосованих гуманітарних інтервенцій без мандату Ради Безпеки ООН. The problem of Legitimacy of humanitarian intervention in the modern international relations has been clarified in the article. Humanitarian intervention was defined as any kind of foreign intervention into the territory of the state with a use of force aiming to protect the rights of its citizens or foreign citizens when ruling elite of this state has no wish or doesn’t want to do it independently. It has been specified that the basis for intervention outside expect the violation of human rights and citizens in the certain state is usually a civil war. Based on the analysis of the intervention documents the main contradictions concerning the legality of the usage of humanitarian interventions in practice have been defined. The attention has been focused on the contradiction in the international law concerning the permit (article 42 of the UN Charter) and prohibition (article 2) of international humanitarian intervention. The kinds of humanitarian intervention have been distinguished. They are: unilateral humanitarian intervention, collective humanitarian intervention under the aegis of the United Nations ahd humanitarian intervention under the aegis of regional international organizations. The peculiarities of the applied interventions without the mandate of the UN security Council have been examined. The causes of the deligitimation of the practical usage of humanitarian intervention in the international relations have been outlined. They are in the effectiveness of the principles of the interfernce, non-use of the force or the threat of force, peaceful settlement of international disputes, sovereign equality of states, etc.
The problem of legitimacy of humanitarian interventions in the modern international relations
Keywords: гуманітарна інтервенція; легітимність; міжнародні виклики; міжнародне право; миротворчі операції; права людини; геноцид; державний суверенітет; humanitarian intervention; international relations; legality; humanitarian aid; international law; peace-making operations; human rights; genocide; state sovereignty